Modeling uncertainty in the earth sciences - Caers, Jef.; Wiley InterScience (Online service) (Hoboken, NJ : Wiley, 2012)
Modeling Uncertainty in the Earth Sciences highlights the various issues, techniques and practical modeling tools available for modeling the uncertainty of complex Earth systems and the impact that it has on practical situations. The aim of the book is to provide an introductory overview which covers a broad range of tried-and-tested tools. Descriptions of concepts, philosophies, challenges, methodologies and workflows give the reader an understanding of the best way to make decisions under uncertainty for Earth Science problems. The book covers key issues such as: Spatial and time aspect; larg.
Front Matter -- Introduction -- Review on Statistical Analysis and Probability Theory -- Modeling Uncertainty: Concepts and Philosophies -- Engineering the Earth: Making Decisions Under Uncertainty -- Modeling Spatial Continuity -- Modeling Spatial Uncertainty -- Constraining Spatial Models of Uncertainty with Data -- Modeling Structural Uncertainty -- Visualizing Uncertainty -- Modeling Response Uncertainty -- Value of Information -- Example Case Study -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Geology -- Mathematical models; Earth sciences -- Statistical methods; Three-dimensional imaging in geology; Uncertainty; Earth sciences -- Statistical methods; Geology -- Mathematical models; Three-dimensional imaging in geology; Uncertainty; Geology; Science; SCIENCE -- Environmental Science (see also Chemistry -- Environmental); Earth sciences -- Statistical methods; Geology -- Mathematical models; Three-dimensional imaging in geology; Uncertainty; Electronic books